Decolonization reconsidered: Rebirths, continuities and erasures - Ginio, Ruth; Schler, Lynn (Hagar: Studies in Society and Culture, 2010)
The year 2010 marks the fiftieth anniversary of what was widely proclaimed the "Year of Africa", when seventeen former colonies in Africa received their independence from European colonial rule.